Regulation by molecular oxygen and organic substrates of hydrogenase synthesis in Alcaligenes eutrophus. - Cangelosi, G A (1984)
Chemoautotrophic growth of Alcaligenes eutrophus 17707 is inhibited by 20% oxygen in the gas phase. Lowering the oxygen concentration to 4% results in chloramphenicol-sensitive derepression of soluble and membrane-bound hydrogenase activity (and of soluble hydrogenase antigen), showing that oxygen inhibition is due at least in part to repression of hydrogenase synthesis. Mutations resulting in derepression of hydrogenase activity (and antigen) under 25% oxygen (Ose-) mobilized with a self-transmissable plasmid which is already known to carry genes necessary for hydrogenase expression. Plasmid-borne mutations resulting in loss of soluble hydrogenase activity have no effect on the Ose phenotype, but chromosomal mutations resulting in reduction or loss of both hydrogenase activities cannot be made Ose-. The Ose- mutation does not alter the thermostability of either hydrogenase, and soluble hydrogenase in the mutant reacts with complete identity with that of the wild type, indicating that the Ose- phenotype does not result from structural alterations in either enzyme. Ose- mutants are also relieved of normal hydrogenase repression by organic substrates, which aggravates hydrogenase-mediated inhibition of heterotrophic growth by hydrogen. Regulation of hydrogenase in Ose- strains of A. eutrophus 17707 is nearly identical to that of wild-type A. eutrophus strains H1 and H16.